Pain and Disgust: The Facial Signaling of Two Aversive Bodily Experiences - Kunz, Miriam; Peter, Jessica; Huster, Sonja; Lautenbacher, Stefan (PLOS ONE, 2013)
The experience of pain and disgust share many similarities, given that both are aversive experiences resulting from bodily threat and leading to defensive reactions. The aim of the present study was to investigate whether facial expressions are distinct enough to encode the specific quality of pain and disgust or whether they just encode the similar negative valence and arousal level of both states. In sixty participants pain and disgust were induced by heat stimuli and pictures, respectively. Facial responses (Facial Action Coding System) as well as subjective responses were assessed. Our main findings were that nearly the same single facial actions were elicited during pain and disgust experiences. However, these single facial actions were displayed with different strength and were differently combined depending on whether pain or disgust was experienced. Whereas pain was mostly encoded by contraction of the muscles surrounding the eyes (by itself or in combination with contraction of the eyebrows); disgust was mainly accompanied by contraction of the eyebrows and—in contrast to pain—by raising of the upper lip as well as the combination of upper lip raise and eyebrow contraction. Our data clearly suggests that facial expressions seem to be distinct enough to encode not only the general valence and arousal associated with these two bodily aversive experiences, namely pain and disgust, but also the specific origin of the threat to the body. This implies that the differential decoding of these two states by an observer is possible without additional verbal or contextual information, which is of special interest for clinical practice, given that raising awareness in observers about these distinct differences could help to improve the detection of pain in patients who are not able to provide a self-report of pain (e.g., patients with dementia).